Ein Beitrag über Arbeitszeitfunktionen in der Feldwirtschaft - Schäfer, Winfried (de, 1977)
Through the application of the Set Theory, the definitve and evaluation regions of field-time functions have been established. Using a systematics of field-time functions, possible models of association were treated. Finally, field-time functions for those cases that are not transport-related tasks are presented, and the determination of field-time with the use of Nomogrammes is illustrated as an example
Functions for calculation of working time in crop production
Keywords: Ra; maanmuokkauskoneet; työnmenekki; working time; crop production; calculation